SEJARAH MASUKNYA AJARAN ISLAM DAN PENDIDIKAN ISLAM DI MASA KESULTANAN GOWA - Abdul Mukti; Yusnaili Budianti; Faisal Faisal; Muhammad Nazri; Muhammad Amran (Jurnal Ilmiah Hospitality, 2022)
This paper describes the transformation of the historical system of entry and the educational process of Islamic teachings in South Sulawesi which touched the sultanates of Gowa and Tallo. Of course, all of this must be examined from the history of the kingdom, the customs of the people, and the beliefs of the people before embracing Islam and after embracing the teachings of Islam. Of course the question will arise who is the bearer of Islamic teachings, and how the process of education for Islamic teachings in the sultanates of Sulawesi, the sultanates of Gowa and Tallo will arise. From this important question, the writer concludes that the entry of Islamic religious teachings brought by scholars from outside the region and applying science by paying attention to the suitability of cultural cults and customs of different people in Sulawesi, especially in the sultanates of Gowa and Tallo. In the end, the long and systematic process of the ulama figures in concocting Islamic education resulted in results which until now have made him one of the largest adherents of the Islamic religion in the archipelago.